2017
DOI: 10.1016/j.worlddev.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Did FDI Really Cause Chinese Economic Growth? A Meta-Analysis

Abstract: This study performs a meta-analysis of research that estimates the relationship between FDI and Chinese economic growth. Our sample includes 37 studies and a total of 280 estimates. We include both English-and Chinese-language studies. Our initial "raw" finding is that FDI has had a substantial, positive impact on Chinese economic growth. Furthermore, our results suggest that the effect is not inflated by endogeneity, nor impacted by publication bias. However, the positive effect is found to be smaller for mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 61 publications
2
76
0
Order By: Relevance
“…This condition shows that there is a causality relationship from foreign direct investment to the economic growth. Tan and Tang (2016), Afşar (2008), Andraz and Rodrigues (2010) and Gunby et al (2017) also underlined the same conclusion in their studies. Therefore, it can be said that developing countries should give importance to attract foreign investors to provide economic improvement.…”
Section: Analysis Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…This condition shows that there is a causality relationship from foreign direct investment to the economic growth. Tan and Tang (2016), Afşar (2008), Andraz and Rodrigues (2010) and Gunby et al (2017) also underlined the same conclusion in their studies. Therefore, it can be said that developing countries should give importance to attract foreign investors to provide economic improvement.…”
Section: Analysis Resultssupporting
confidence: 53%
“…Similar to this study, Chakraborty and Basu (2002) also emphasized the same issue for India by using Vector Error Correction Method. Moreover, Kottaridi and Stengos (2010), Anwar and Nguyen (2010), Makki and Somwaru (2004), Tan and Tang (2016), Afşar (2008), Andraz and Rodrigues (2010), Gunby et al (2017) and Iqbal et al (2010) underlined the importance of foreign direct investment in economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, Yalta () employed a simulation‐based test and found that a statistically substantial connection between FDI inflows and GDP growth does not exist. However, Gunby et al () suggested that FDI‐linked productivity spillovers are not significantly associated with Chinese economic growth. Analysing the FDI, growth, and exports association, Ahmad et al () found a bi‐directional causal link between FDI and economic growth for ASEAN countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors indicated that productivity spillovers can be identified as the key element of FDI stimulating process on economic growth. According to the authors' conclusion "the effect of FDI on Chinese economic growth is much smaller than one would expect from a naïve aggregation of existing estimates" (Gunby et al, 2017).…”
Section: Introductionmentioning
confidence: 97%